The History Of Commandaria: Digital Journeys Back To Time - Papadopoulos, Constantinos; Tsapatsoulis, Nicolas; Kounoudes, Anastasis; Lanitis, Andreas (My University, 2008)
Commandaria is considered one of the oldest types of wines and it has been ranked as one of the best wines of the last millennium. Production of Commandaria in Cyprus is associated with historical and political events that took place at the island, especially during the last millennium, hence studies related to Commandaria are heavily related to the culture and history of Cyprus. Unfortunately up to now the issue of preserving the history and traditions related to the production of Commandaria over the years did not receive adequate attention and as result the danger of losing important aspects of the relevant Cypriot cultural heritage is obvious. With our work we aim to develop an interactive system through which the history of the production of Commandaria at different areas in Cyprus and different time periods will be presented along with historical events that took place in the island and can be related with Commandaria production. As part of the project we will establish a multimedia digital library that will contain items related to the history and production of Commandaria in Cyprus. All multimedia database entries will be sorted according to various criteria, including the chronological period, the geographical location they refer to and the actual contents of the item, and could be searched via semantic-based queries with the aid of an ontology. In addition, an interactive application will be created where users will have the opportunity to explore the history of Commandaria in Cyprus at different geographical locations and different time periods. The final system will operate both as a web application and as a stand alone application in information kiosks. The system we plan to develop will be most useful for preserving traditions related to the production of Commandaria and support efforts of researchers who wish to explore the history of Commandaria and Cypriot culture as well as the great public for educational and entertainment purposes.
Keywords: Interactive environments; Tools for education; Documentation and training in CH; Semantic Processing in CH